Innovative IoT-Based Automatic Gate System with RFID and Electro-Magnetic Lock for Secure Access - David Fadlianda; Muhammad Fikry; Nunsina (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
In this study, we developed an innovative IoT-based automatic gate system aimed at enhancing security and providing flexible access control. The system incorporates an ESP32 microcontroller with integrated Wi-Fi, enabling seamless remote access via mobile devices. It also features RFID technology for reliable physical access control when an internet connection is unavailable. To ensure user safety, an HC SR-04 ultrasonic sensor is implemented to detect obstacles during gate movement, preventing potential accidents. The security of the system is further reinforced by a dual-layer mechanism utilizing an electromagnetic lock (Emlock), which activates upon gate closure to prevent unauthorized access and deactivates when the gate opens. Experimental results indicate that the system effectively addresses the shortcomings of conventional gate control methods, delivering improved security, convenience, and safety for users. Performance tests confirm the reliable operation of both RFID and mobile control functions, with minimal delays observed in sensor response times. This comprehensive solution is well-suited for residential and commercial properties, offering a modern approach to automatic gate security.